Fabrication of 3D high aspect ratio PDMS microfluidic networks with a hybrid stamp1. Issue 8 (21st April 2015) - Kung, Yu-Chun; Huang, Kuo-Wei; Fan, Yu-Jui; Chiou, Pei-Yu
<x xml:space="preserve">Abstract</x> We report a novel methodology for fabricating large-area, multilayer, thin-film, high aspect ratio, 3D microfluidic structures with through-layer vias and open channels that can be bonded between hard substrates.